Gender roles and human capital investment : the relationship between traditional attitudes and female labour market performance - Vella, Francis [Verfasser] (My University, 1994)
"This paper investigates the relationship between the labour market behaviour of females and their attitudes towards traditional gender roles. An attitudes index is constructed by employing individuals' responses to statements related to the role of women and examined to determine whether it is correlated with individual characteristics. The paper examines whether these attitudes influence human capital attainment and whether they are weakly exogenous to educational attainment.- It also focuses on the impact of these traditional attitudes upon labour supply and the return to education. The results are dramatic. It is found that females' attitudes towards working women are developed in their youth and results in substantial reductions in their human capital investment, labour supply and rates of return to education. Furthermore, it is found that these attitudes are determined outside the educational process." (author's abstract, IAB-Doku) ((en)) Der Artikel untersucht anhand einer Befragung von australischen Frauen Zusammenhänge zwischen der Einstellung der Frauen zu traditionellen Geschlechterrollen und ihrem Erwerbsverhalten bzw. ihrer Bereitschaft, in Humankapital zu investieren. (IAB)
Geschlechterrolle und Humankapitalinvestition; die Beziehung zwischen traditionellen Einstellungen und dem weiblichen Erwerbsverhalten
Keywords: G 2.4.5 Gender Mainstreaming; S 4.3.6 Human Capital; G 1.3.2 Bildungsverhalten und -verläufe; G 1.2 Arbeitsmarkt; Frauen; Einstellung; Geschlechterrolle; Humankapital; Bildungsverhalten; Erwerbsverhalten; Quantitative Angaben